The role of peer observation and peer review in the professional formation and development of American and british higher education teachers - Belmaz, Yaroslava; Otroshko, Tamara (My University, 2024)
In the article peer observation and peer review are defined as effective forms of professional development of higher education teachers. For illustrative purpose experience of the USA and Great Britain is given. In defining the concept of "professional development", the works of American and British teachers who use different definitions are analysed: "professional development", "career development", "staff development", etc. It is noted that professional development is usually seen as a process aimed at improving skills through formal or informal learning. Professional development should be related to the needs of the individual and be consistent with the current situation in society and education. The authors emphasise that peer observation and peer evaluation as a form of professional development of higher education teachers are increasingly used in higher education institutions in the USA and the UK, receiving support from organisations involved in improving the quality of learning and teaching in higher education. The paper emphasises that peer observation is not a control or critical evaluation of teaching activities. It is seen as a support system and a means of professional development of the teaching staff. The advantages of peer observation are analysed both for those teachers who are observers and for those whose classes are observed. The authors note that there are formative (developmental) and summative (for solving personnel issues) peer observation. In the process of peer observation, three stages can be distinguished: preparatory (instruction), observation as such, or attendance at a class, and final (feedback and analysis). The article analyses all of these stages in detail, emphasising the importance of each of them. Particular emphasis is placed on feedback, without which it is impossible to achieve the effectiveness of peer observation. As an example, the article provides recommendations for visiting, observing and analysing classes during a peer observation at Keele University and the Center for Effective Learning and Teaching at North Carolina State University.
Belmaz Y. The role of peer observation and peer review in the professional formation and development of American and british higher education teachers / Y. Belmaz, T. Otroshko // Проблеми інженерно-педагогічної освіти, 2024. – № 82. – С. 269–274
Keywords: взаємовідвідування, взаємоспостереження, взаємооцінювання, викладач вищої школи, професійний розвиток, зворотній зв’язок, США, Велика Британія; peer observation, peer review, peer evaluation, higher education teacher, professional development, feedback, the USA, Great Britain